(untitled) - Claverie, Jean-Michel. (Hoboken, 2007)
This easy-to-follow guide leads you step by step through every bioinformatics task that can be done over the Internet. Forget long equations, computer-geek gibberish, and installing bulky programs that slow down your computer
Keywords: Bioinformatics.,Computational Biology.,Bio-informatica.,Sinh học máy tính